2008
DOI: 10.4161/cc.7.13.6147
|View full text |Cite
|
Sign up to set email alerts
|

IKKα enhances human keratinocyte differentiation and determines the histological variant of epidermal squamous cell carcinomas

Abstract: Squamous cell carcinomas (SCCs) of the skin display different clinical features according to their epithelial differentiation grade and histological variant. Understanding the causes of these divergences might increase the curability of SCCs. Therefore, it is important to study the mechanisms of differentiation in keratinocytes. IKK (IkappaB kinase) alpha is an important protein for epidermal morphogenesis, although the pathways through which it exerts its function are unknown and controversy exists about its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 40 publications
9
30
0
Order By: Relevance
“…Consistent with a role in epidermal homeostasis, IKKa functions as a cofactor for Smad2/ 3 in a Smad4-independent pathway that inhibits keratinocyte proliferation [13,28]. Consequently, IKKa deficient mice display a hyperplasic epidermal phenotype [29,42], whereas animals overexpressing IKKa in the suprabasal skin compartment showed increased epidermal differentiation and are resistant to chemically induced SCC [23]. In the same direction, truncating (inactivating) mutations in the IKKa gene are consistently found in human and mouse SCC lesions [32].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Consistent with a role in epidermal homeostasis, IKKa functions as a cofactor for Smad2/ 3 in a Smad4-independent pathway that inhibits keratinocyte proliferation [13,28]. Consequently, IKKa deficient mice display a hyperplasic epidermal phenotype [29,42], whereas animals overexpressing IKKa in the suprabasal skin compartment showed increased epidermal differentiation and are resistant to chemically induced SCC [23]. In the same direction, truncating (inactivating) mutations in the IKKa gene are consistently found in human and mouse SCC lesions [32].…”
Section: Introductionmentioning
confidence: 74%
“…In the same direction, truncating (inactivating) mutations in the IKKa gene are consistently found in human and mouse SCC lesions [32]. Unexpectedly, we and others recently demonstrated that IKKa activity is significantly increased in a set of human SCC samples [29,30]. We here investigate whether IKK activity influences cSCC behaviour, and which is the effect of targeting IKK in this particular cancer cell type.…”
Section: Introductionmentioning
confidence: 84%
“…Its expression is almost negative in keratinizing nasopharyngeal carcinoma but higher in non-keratinizing nasopharyngeal carcinoma [42]. In epidermal squamous cell carcinomas, IKK1 enhances human keratinocyte differentiation and regulates histological variants [43]. IKK1 is upregulated to control metastasis by repressing maspin in PDAC [44].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…On the contrary, keratin K8, a marker of malignancy in skin tumors (Casanova et al, 2004) showed extensive staining in the C57-CYLD C/S carcinomas and weak expression in the C57-Control tumors (Figure 5a). K13, a keratin characteristic of internal stratified squamous epithelia, which is aberrantly expressed in skin tumors and is also considered a marker of tumor progression (Winter et al, 1990;Moreno-Maldonado et al, 2008) was also highly expressed in the C57-CYLD C/S tumors and it was hardly detected in the C57-Control SCCs (Figure 5a). These data confirm that the tumors arising from C57-CYLD C/S cells are more aggressive that those from control cells.…”
Section: The Expression Of Cyld C/s In Tumoral Epidermal Cells Increamentioning
confidence: 99%